Economic boom and social mobility: The Irish experience - Christopher T. Whelan; Richard Layte (The Economic and Social Research Institute (ESRI), 2004)
In this paper we examine the consequences for social mobility patterns of the unprecedented period of economic growth experienced in Ireland over the 1990s and the implications of developments for current theories of social fluidity. Contrary to suggestions that the 'Celtic Tiger' experience has been associated with a deepening problem of marginalization we found evidence for a substantial upgrading of the class structure and increased levels of social mobility. We also found evidence for increased social fluidity in relation to long-range hierarchical mobility. Such increased openness could not be explained by changes in the manner in which education mediates the relationship between origins and destinations. There is no necessary relationship between economic growth and social fluidity. However, the pattern of change over time in the Irish case suggests that both long-term factors associated with the upgrading of the class structure and short-term factors reflected in the unprecedented tightness of the labour market have produced a situation where employers have increasingly applied criteria other than education in a manner that has facilitated increased social fluidity. The Irish case provides further support to the argument for reconsidering the balance that mobility research has struck between social fluidity and absolute mobility and encouraging increased attention to the evolution of firms and jobs. It also provides support for the conclusion, that in circumstances where policies in advanced industrial societies have shown an increasing tendency to diverge, increased social fluidity may come about as a consequence of very different economic and social policies.
Keywords: 330